2017
DOI: 10.1111/2041-210x.12763
|View full text |Cite
|
Sign up to set email alerts
|

Radar wind profilers and avian migration: a qualitative and quantitative assessment verified by thermal imaging and moon watching

Abstract: Summary Radars of various types have been used in ornithological research for about 70 years. However, the potential of radar wind profiler (RWP) as a tool for biological purposes remains poorly understood. The aim of this study is to assess the suitability of RWP for ornithological research questions. A 1290 MHz RWP at the south‐eastern coast of the Bay of Biscay has been known to exhibit seasonally occurring nocturnal signals attributed to migrating birds. As a first step to verify the origin of these seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Consistent with this expectation, Weisshaupt et al. () found that long‐range IR detectability decreased considerably with precipitation and cloud cover when compared to radar detections.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Consistent with this expectation, Weisshaupt et al. () found that long‐range IR detectability decreased considerably with precipitation and cloud cover when compared to radar detections.…”
mentioning
confidence: 74%
“…, Weisshaupt et al. ) and quantifying detection rates of white‐tailed deer ( Odocoileus virginianus ) through simultaneous spotlight and IR surveys (Collier et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical bird profiles were extracted every 5 min from 133 m up to 2000 m a.g.l. Details on bird extraction procedure from this radar system and the calculation of the MTRs adapted to the respective data collection mode are given in Weisshaupt et al (2017). This radar is referred to as radar wind profiler (RWP).…”
Section: Bay Of Biscaymentioning
confidence: 99%
“…Therefore, a reason for the much lower MTR might be due to a reduced detection probability for small passerines with distance, reinforced by the relatively long wave-length. For the RWP a first inventory of features and echo strengths has been provided for various targets (Weisshaupt 2015, Weisshaupt et al 2017. However, echoes included in the MTR calculations had to be close to the beam center to be recognized as birds (Weisshaupt et al 2017).…”
Section: Technical Aspectsmentioning
confidence: 99%